Traditional Inland Fishing Practices in Bhadrak district of Odisha, India - Panda, Taranisen; Mishra, Nirlipta; Rahimuddin, Shaik; Pradhan, Bikram K.; Mohanty, Raj Ballav (International Journal of Scientific Research in Biological Sciences, 2023)
This paper focuses on traditional fishing methods practiced by the fisherfolk communities of Bhadrak district, Odisha, India. Fifty-nine informants were selected for the study to enlist the varieties of fishing techniques that the people use to capture fish. Using a semi-structured questionnaire, data were collected through personal interviews and direct observation. A total of 15 handmade fishing devices made up of locally available resources are used to catch fish in freshwater bodies. The fisherfolk develop some unique fish-catching devices like Pohala and Bankia which ensure eco-friendly utilization of freshwater fishery resources without affecting the fish diversity in aquatic habitats. However, destructive fishing practices with fine mesh nets (e.g., masari jal) have also been noticed. Prominent fish species and prawns captured by using fishing devices include Amblypharyngodon mola (Hamilton, 1822), Anabas testudineus (Bloch, 1792), Channa striata (Bloch, 1793), Glossogobius giuris (Hamilton, 1822), Macrobrachium rosenbergii (De Man, 1879), Mystus gulio (Hamilton, 1822), Pethia conchonius (Hamilton, 1822), Wallago attu (Bloch & Schneider,1801) and Xenentodon cancila (Hamilton, 1822). The present investigation provides traditional knowledge-based fishing devices that may help proper management of fish resources in inland water bodies. Our findings affirm that fishers of the region still adopt the conventional method of fishing which affords substantial contributions to their livelihood. The challenge of using fine mesh nets can be overcome by creating awareness among the fishers.